2016
DOI: 10.2147/ott.s94236
|View full text |Cite
|
Sign up to set email alerts
|

Influence of negative lymph node in No 7 on survival of patients with middle thoracic esophageal squamous cell carcinoma

Abstract: BackgroundThe overall survival (OS) of patients with thoracic esophageal cancer is poor because of the high rate of lymph node metastases. However, recent studies found that the negative lymph node (LN) may also influence the patients’ OS. The purpose of this study is to investigate which negative LN stations play a key role in OS prediction.MethodOur study included the retrospective records of 99 patients, who were identified with middle thoracic esophageal squamous cell cancer after esophagectomy. The maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Ma et al [13] demonstrated that ESCC patients with more than 20 NLNs have better survival rates in contrast to those with less than or equal to 20 NLNs, through retrospective analysis of 381 patients who had underwent surgical resection. Zhang et al [19] retrospectively analyzed 99 patients who were identified with middle thoracic ESCC after esophagectomy and found obvious differences of OS between the following groups: patients with more than and less than 10 NLNs and patients with>15 and ≤15 NLNs. Based on the above research evidences, we categorizes the NLNs into 4 groups (0-9, 10-14, 15-19 and ≥20 NLNs) to further explore the relationship between the number of NLNs and prognosis of patients with ESCC after curative esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [13] demonstrated that ESCC patients with more than 20 NLNs have better survival rates in contrast to those with less than or equal to 20 NLNs, through retrospective analysis of 381 patients who had underwent surgical resection. Zhang et al [19] retrospectively analyzed 99 patients who were identified with middle thoracic ESCC after esophagectomy and found obvious differences of OS between the following groups: patients with more than and less than 10 NLNs and patients with>15 and ≤15 NLNs. Based on the above research evidences, we categorizes the NLNs into 4 groups (0-9, 10-14, 15-19 and ≥20 NLNs) to further explore the relationship between the number of NLNs and prognosis of patients with ESCC after curative esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the site of PLN and NLN that are removed during lymphadenectomy may be a more important predictor of prognosis than the number of PLN and NLN (9,10). In our previous study, we also con rmed that certain sites of NLN may play important roles in the prognosis of patients with ESCC (11).…”
Section: Introductionmentioning
confidence: 56%